Combined analysis of transcriptome and metabolome reveals the molecular mechanism and candidate genes of Haloxylon drought tolerance - Yang, Fang; Lv, Guanghui (Frontiers in Plant Science, 2022)
Haloxylon ammodendron and Haloxylon persicum, as typical desert plants, show strong drought tolerance and environmental adaptability. They are ideal model plants for studying the molecular mechanisms of drought tolerance. Transcriptomic and metabolomic analyses were performed to reveal the response mechanisms of H. ammodendron and H. persicum to a drought environment at the levels of transcription and physiological metabolism. The results showed that the morphological structures of H. ammodendron and H. persicum showed adaptability to drought stress. Under drought conditions, the peroxidase activity, abscisic acid content, auxin content, and gibberellin content of H. ammodendron increased, while the contents of proline and malondialdehyde decreased. The amino acid content of H. persicum was increased, while the contents of proline, malondialdehyde, auxin, and gibberellin were decreased. Under drought conditions, 12,233 and 17,953 differentially expressed genes (DEGs) were identified in H. ammodendron and H. persicum, respectively, including members of multiple transcription factor families such as FAR1, AP2/ERF, C2H2, bHLH, MYB, C2C2, and WRKY that were significantly up-regulated under drought stress. In the positive ion mode, 296 and 452 differential metabolites (DEMs) were identified in H. ammodendron and H. persicum, respectively; in the negative ion mode, 252 and 354 DEMs were identified, primarily in carbohydrate and lipid metabolism. A combined transcriptome and metabolome analysis showed that drought stress promoted the glycolysis/gluconeogenesis pathways of H. ammodendron and H. persicum and increased the expression of amino acid synthesis pathways, consistent with the physiological results. In addition, transcriptome and metabolome were jointly used to analyze the expression changes of the genes/metabolites of H. ammodendron and H. persicum that were associated with drought tolerance but were regulated differently in the two plants. This study identified drought-tolerance genes and metabolites in H. ammodendron and H. persicum and has provided new ideas for studying the drought stress response of Haloxylon.